1987
DOI: 10.1104/pp.85.3.841
|View full text |Cite
|
Sign up to set email alerts
|

The Timing and Rate of Phytic Acid Accumulation in Developing Soybean Seeds

Abstract: The time-course of phosphorus (P) accumulation in the phytic acid fraction of developing soybean (Glycine max [L.] Merr. cv 'Williams 79') seeds as well as the relation of phytic acid P to total P content were determined. Phytic acid was detected early in embryogenesis in fieldgrown soybeans and accumulated in a linear fashion throughout most of seed development. Although the observed rates of accumulation ranged from 18.7 micrograms phytic acid P per seed per day in pods positioned low on the plant to 33.6 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
45
1
1

Year Published

1989
1989
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(54 citation statements)
references
References 16 publications
7
45
1
1
Order By: Relevance
“…At the same time, however, Raboy and Dickinson (1987) used phosphate starvation during seed development to produce soybean (Glycine max) seeds with greatly reduced phytic acid and convincingly showed that phytic acid is not a requirement for seed viability or germination. Mutant lines with greatly reduced levels of phytic acid have been described in maize (Zea mays; Raboy et al, 2000), barley (Hordeum vulgare;Larson et al, 1998), rice (Oryza sativa; Larson et al, 2000), and most recently soybean (Sebastian et al, 2000;Wilcox et al, 2000).…”
mentioning
confidence: 99%
“…At the same time, however, Raboy and Dickinson (1987) used phosphate starvation during seed development to produce soybean (Glycine max) seeds with greatly reduced phytic acid and convincingly showed that phytic acid is not a requirement for seed viability or germination. Mutant lines with greatly reduced levels of phytic acid have been described in maize (Zea mays; Raboy et al, 2000), barley (Hordeum vulgare;Larson et al, 1998), rice (Oryza sativa; Larson et al, 2000), and most recently soybean (Sebastian et al, 2000;Wilcox et al, 2000).…”
mentioning
confidence: 99%
“…), phytic acid is deposited in protein bodies (protein storage vacuoles) as a complex of chelated minerals and protein known as phytin (Prattley and Stanley, 1982). Maximal phytic acid levels are achieved at seed maturity immediately preceding desiccation (Raboy and Dickinson, 1987) and represent approximately 1% of the total weight in dry seeds.…”
mentioning
confidence: 99%
“…
Perhaps the single most distinctive feature of plant inositol phosphate metabolism is the accumulation of inositol hexakisphosphate (InsP 6 ) 2 to levels up to several percent of dry weight in seed or storage tissues (Raboy and Dickinson, 1987) and in vegetative tissues to levels that are likely to be in excess of other inositol phosphates. It is likely that the inositol phosphates commonly found in plants are not related to the signaling molecule Ins(1,4,5) P 3 , but are intermediates of the pathways of InsP 6 synthesis and breakdown.

We have described a number of inositol phosphates in the duckweed Spirodela polyrhiza (Brearley and Hanke, 1996a) and in barley aleurone tissue (Brearley and Hanke, 1996c).

…”
mentioning
confidence: 99%